Comic Strips to Facilitate Students Reading Comprehension on Narrative Text - Br Siregar, Ayu Sartika; Fauzana, Riri (State Islamic University of Sultan Syarif Kasim Riau, 2024)
This study was conducted based on students' problems in reading, such as students' low reading comprehension abilities, lack of vocabulary mastery which makes them difficult to understand texts, and also difficulties in pronunciation. Therefore, this research aims to find out whether the use of comic strips improves students' reading comprehension skills in narrative texts, in class X MA Al-Ittihad Tapung Makmur students. This research uses quantitative research. This research was carried out in February-June 2024 at MA Al-Ittihad Tapung Makmur. The population in this study were all class as many as 26 students. The design of this research is a pre-experimental method with one group pre-test and post-test design. To collect data, researchers used a reading test to determine students' reading abilities which consisted of multiple choice questions with 20 questions. The results of data analysis show that the average score of students after being taught using Comic strips (84.04) is higher than before being taught using Comic strips (53.85). It can be concluded that there is an influence between students' reading comprehension abilities before and after being taught using Comic strips in class X MA Al-Ittihad Tapung Makmur.